Autoinducer-2 of quorum sensing is involved in cell damage caused by avian pathogenic Escherichia coli. (October 2016) - Cui, Zhen-Qiang; Wu, Zong-Mei; Fu, Yun-Xing; Xu, Dao-Xiu; Guo, Xun; Shen, Hai-Qing; Wei, Xu-Bin; Yi, Peng-Fei; Fu, Ben-Dong
Abstract: Avian pathogenic Escherichia coli (APEC) infections are responsible for great losses in the poultry industry. Quorum sensing (QS) acts as a global regulatory system that controls genes involved in bacterial pathogenesis, metabolism and protein biosynthesis. However, whether QS of APEC is related to cell damage has not been elucidated. In the present study, we explored the correlation between the damage of chicken type II pneumocytes induced by APEC and the autoinducer-2 (AI-2) activity of APEC. The results showed that when chicken type II pneumocytes were co-cultured with 10 8 CFU/ml of APEC-O78 for 6 h, the release of LDH reached the highest level (192.5 ± 13.4 U/L) (P < 0.01), and the percentages of dead cells followed the same trend in trypan blue exclusion assay. In addition, the AI-2 activity of cell-free culture fluid (CF) reached the maximum value after 6 h co-culture with 10 8 CFU/ml of APEC-O78. At the same time, the mRNA expressions of eight virulence genes ( papC, fimA, fimC, hlyE, ompA, luxS, pfs, and qseA ) of 10 8 CFU/ml APEC-O78 were significantly increased compared with those of 10 7 CFU/ml, and the mRNA expressions of four virulence genes ( hlyE, tsh, iss, and luxS ) of 10 8 CFU/ml APEC-O78 were higher than those of 10 9 CFU/ml (p < 0.05) after incubation for 6 h. These results suggested that AI-2-mediated QS is involved in the cell damage induced by APEC-O78, indicating AI-2 may be one new potential target for preventing chicken colibacillosis. Graphical abstract: Highlights: To establish the optimum AI-2 of APEC-O78 bioluminescence assay. APEC-induced cell damage was correlated with the production of AI-2. AI-2-mediated QS is involved in the cell damage induced by APEC-O78.